2012
DOI: 10.1016/j.aorn.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors, Routines, and Differences Between Perioperative and Non‐perioperative Nurses

Abstract: Despite efforts to reduce the incidence of perioperative medication errors, these errors continue to be a problem. We examined written accounts from 16 nurses who discussed medication errors in the perioperative environment and 11 nurses who provided additional information about perioperative errors, nursing education, and the state of health care. Preoperative medication errors were the most frequently reported perioperative medication errors. Other reported errors involved intraoperative medication administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Evidências apontam que os profissionais de saúde desenvolvem um trabalho no qual pode ocorrer erros de medicação, entretanto, as condições de trabalho oferecidas pelas instituições de saúde têm forte influência na geração do erro (4) . O déficit na força de trabalho, que gera a sobrecarga de trabalho tem significativa ligação com os erros de medicação, problemática essa que precisa ser considerada pelos gestores dos serviços de saúde e pelos formuladores de políticas (4,49,50) . Por isso, pensar a segurança do paciente requer necessariamente repensar as condições de trabalho da enfermagem.…”
Section: Discussionunclassified
“…Evidências apontam que os profissionais de saúde desenvolvem um trabalho no qual pode ocorrer erros de medicação, entretanto, as condições de trabalho oferecidas pelas instituições de saúde têm forte influência na geração do erro (4) . O déficit na força de trabalho, que gera a sobrecarga de trabalho tem significativa ligação com os erros de medicação, problemática essa que precisa ser considerada pelos gestores dos serviços de saúde e pelos formuladores de políticas (4,49,50) . Por isso, pensar a segurança do paciente requer necessariamente repensar as condições de trabalho da enfermagem.…”
Section: Discussionunclassified
“…In six studies nurse shortage was reported to be one of the main causes that might lead to MAEs. [34][35][36][37][38] On the other hand, heavy staff workloads in three studies appeared to be a major leading factor to MAEs. [39][40][41] Many studies have linked nurse shortage with increased workloads which in turn are both related MAEs.…”
Section: Methodsmentioning
confidence: 99%
“…The use of focus groups is supported in the literature, and researchers have used this method in several recent phenomenological research designs in nursing and other health professions . Specific to perioperative nursing, researchers have used focus groups related to the role of OR nurses in patient safety and perceptions of nurses, anesthesia providers, and surgeons on quality improvement measures to increase intraoperative patient safety …”
Section: Methodsmentioning
confidence: 99%
“…Overall, limited research exists regarding nursing errors from the perspectives and personal experiences of perioperative nurses. Researchers have focused primarily on medication errors in the perioperative environment and retained surgical items . Several studies have centered on the use of checklists and briefings to prevent adverse patient outcomes .…”
Section: Literature Reviewmentioning
confidence: 99%